Accelerated carbonation of ball-milling modified MSWI fly ash: Migration and stabilization of heavy metals. Issue 2 (April 2023) - Chen, Jie; Shen, Yizhe; Chen, Zhiliang; Fu, Congkai; Li, Minjie; Mao, Tieying; Xu, Ruiyang; Lin, Xiaoqing; Li, Xiaodong; Yan, Jianhua
Abstract: Mechanical ball-milling is an effective technique to reduce particle size, increase lattice defects, and enhance the activity of materials. After mechanical ball-milling modification, an accelerated carbonation technology of municipal solid waste incineration fly ash (FA) was proposed. The effects of ball-milling on carbonation efficiency, heavy metals stabilization, and heavy metals leaching characteristics were investigated. The results showed that the initial carbonation efficiency of ball-milled FA (MFA) was higher than that of the original FA (OFA) because of the in-situ carbonation reaction and the stability of Pb, Cu, and Cd in MFA was improved. The carbonation reaction of MFA was conducted thoroughly by the elevated ionic strength and mass transfer efficiency. The surface of carbonated OFA (COFA) and carbonated MFA (CMFA) stacked calcium carbonation in loose strips and compact spherical respectively, relating to the initial morphology. The dechlorination of CMFA was superior to COFA because the more in-depth carbonation eluted the chlorine from Friedel's salt. The leaching concentrations of heavy metals in CMFA were lower than those in COFA, especially the immobilization efficiency of Pb and Zn reached 99.8 % and 98.5 %, respectively, contributed by the conversion of the Pb and Zn from ionic hydroxides to stable carbonates. Due to the low acid neutralization capacity of CMFA, when the pH dropped from 7 to 5, the heavy metals carbonate chemical precipitation dissolved, and the effect of calcium carbonation on heavy metals wrapping and adsorption disappeared, therefore the subsequent disposal of CMFA should avoid an acidic environment. Graphical Abstract: ga1 Highlights: CO2 is produced by the oxidation of organic carbon in FA during ball milling. MSWI FA undergoes an in-situ carbonation reaction during the ball milling process. The carbonation depth of MFA by high ionic strength and mass transfer increased. The solidification efficiency of Pb and Zn in CMFA is above 98.5 %. Dechlorination of CMFA is superior to COFA due to the more in-depth carbonation.